BMI Categories And Their Relationship With Postural Deformities In Male School Children: A Study From Urban Gwalior (Journal of Namibian Studies : History Politics Culture, 2023)
The focus of this study: This study aims to assess the relationship between BMI categories and postural deformities in male schoolchildren from urban Gwalior. Materials and methods: A total of 2,495 samples were chosen. Samples were obtained from schools located in the urban areas of the Gwalior Region, Madhya Pradesh. The subjects' ages varied from 8 to 12 years, and they were chosen from all categories of schools. The participants were chosen by multi-stage cluster selection from schools in the Gwalior Region. Results: Kyphosis was identified as strongly positive (p 0.05) between Lordosis and overweight at a 5% significance level in the metropolitan districts of the Gwalior Region. Scoliosis was substantially (p